Associations between phthalate metabolites and two novel systemic inflammatory indexes: a cross-sectional analysis of NHANES data - Fangyu Cheng; Yueyuan Li; Kai Deng; Xinyu Zhang; Wenxue Sun; Xin Yang; Xiaofang Zhang; Chunping Wang (Annals of Medicine)
Background The potentially risky effects of metabolites of phthalates (mPAEs) on inflammation and immune function have attracted much attention in recent years. However, direct studies on the relationship between these metabolites and the systemic immune inflammatory index (SII) and systemic inflammatory response index (SIRI) are limited.Methods This cross-sectional study used generalized linear regression models (GLM), restricted cubic splines (RCS), weighted quantile sum (WQS), and Bayesian kernel-machine regression (BKMR) to analyze data from 2,763 U.S. adults aged between 20 and 80 years, obtained from the U.S. National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2018. The study aimed to investigate the relationship between urine samples of nine mPAEs and levels of SII/SIRI in a single, nonlinear, and mixed relationship and explored the robustness of the findings under single and mixed effects using two sensitivity analyses for completeness. In addition, the effects of six variables (age, sex, BMI, the percentage of total daily energy intake from ultra-processed foods (UPFs), total vegetable intake, and dietary supplements) on the association results were explored through subgroup analyses to identify potentially important confounders.Results In single exposure analyses, mono-n-butyl phthalate (MnBP), mono-ethyl phthalate (MEP), and monobenzyl phthalate (MBzP) were positively associated with SII/SIRI. The findings from the two mixed exposure models demonstrated a positive association between the collective concentrations of mPAEs and levels of SII/SIRI, with MBzP being identified as a significant contributor to the urinary levels of mPAEs. The subgroup analysis results of the effects of single and mixed exposures show that the association between mPAEs and SII/SIRI is more significant in females, overweight/obese populations, young/middle-aged populations, and populations with high levels of intake of UPFs.Conclusion Positive associations were identified between mPAEs and SII/SIRI. MBzP was determined to have the most significant impact. The association between mPAEs and SII/SIRI is significantly influenced by female groups, young and middle-aged populations, overweight and obese individuals, as well as those with a higher intake of UPFs.